Symbole w społeczności regionu Zagłębia Dąbrowskiego - Walancik, Marek (Studia Edukacyjne, 2018)
The author attempts to characterize the region of Zagłębie Dąbrowskie, a region on the border between Silesia and Lesser Poland in geographical and cultural sense. He draws attention to the symbolism of the region and its acquaintance and significance in regional identity.